PEMBUATAN PUPUK ORGANIK INTEGRASI AREN-SAPI KELOMPOK TANI-TERNAK “BUKIT HARAPAN” DI DESA LIMBORO RAMBU-RAMBU KECAMATAN SENDANA KABUPATEN MAJENE - Haloho, Ruth Dameria; Irmayanti, Irmayanti; Sari, Dwi Ratna; Rahim, Abdul; Ya'la, Zakirah Raihani; Yeheskiel, Yeheskiel; Rein, Rein; Yosua, Yosua; Nurmalasari, Nurmalasari; Usman, Al Zaima (Jurnal Abdi Insani, 2025)
Fertilizer is one of the strategic elements that plays a role in increasing productivity and unity part of the farming system. The current difficulty for farmers is the scarcity and inaccessibility of fertilizer subsidies, forcing them to seek alternatives to reduce fertilizer purchase costs. An alternative that can be used with organic fertilizer, which can be made using cow dung and aren plant waste, is bokashi fertilizer. The purpose of implementing this Community Service Program is to provide information related to technological innovations in processing aren waste and animal manure as organic fertilizer/compost to increase farmers' income and its application on plants. The implementation method of the activity includes preparation such as location surveys, discussions and explanations on bokashi fertilizer production, outreach and training through material presentation and demonstrations/practice on how to make bokashi fertilizer, as well as monitoring and evaluation. The results of the activity show a significant increase in knowledge and skills among the Bukit Harapan farmer group participants. Before the implementation of the community service activity, the partners' knowledge of waste processing as organic fertilizer was only 4.43%. After the community service activities, the partners' skills increased to 92.29%. The results of the mentoring for the Bukit Harapan Farmers Group were successfully achieved. This is evident from the bokashi, which is mature, has a dark color, a fine texture, and is odorless.